2003
DOI: 10.1073/pnas.1133280100
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule transition-state analysis of RNA folding

Abstract: How RNA molecules fold into functional structures is a problem of great significance given the expanding list of essential cellular RNA enzymes and the increasing number of applications of RNA in biotechnology and medicine. A critical step toward solving the RNA folding problem is the characterization of the associated transition states. This is a challenging task in part because the rugged energy landscape of RNA often leads to the coexistence of multiple distinct structural transitions. Here, we exploit sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
276
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(301 citation statements)
references
References 52 publications
23
276
1
1
Order By: Relevance
“…6B). In support of this model, the formation of a compact intermediate that possesses native tertiary interactions (i.e., correctly oriented helices) is a key step during folding of large RNAs such as ribozymes (Bokinsky et al 2003;Buchmueller and Weeks 2003;Pyle et al 2007;Behrouzi et al 2012). The role of L3 very early in 60S subunit assembly is consistent with this compaction.…”
Section: Discussionsupporting
confidence: 52%
“…6B). In support of this model, the formation of a compact intermediate that possesses native tertiary interactions (i.e., correctly oriented helices) is a key step during folding of large RNAs such as ribozymes (Bokinsky et al 2003;Buchmueller and Weeks 2003;Pyle et al 2007;Behrouzi et al 2012). The role of L3 very early in 60S subunit assembly is consistent with this compaction.…”
Section: Discussionsupporting
confidence: 52%
“…However, NLPB approaches require high-resolution structural data, consider only electrostatic effects, and treat the structure of the RNA as if it were static, as opposed to the dynamic ensemble of conformations that is probably more typical for RNAs in solution. NLPB treatments are therefore most powerful as interpretive aids paired with data from other techniques, as demonstrated in recent studies employing fluorescently labeled helical junctions along with NLPB calculations to investigate junction folding and dynamics (13,16).…”
mentioning
confidence: 99%
“…However, NLPB approaches require high-resolution structural data, consider only electrostatic effects, and treat the structure of the RNA as if it were static, as opposed to the dynamic ensemble of conformations that is probably more typical for RNAs in solution. NLPB treatments are therefore most powerful as interpretive aids paired with data from other techniques, as demonstrated in recent studies employing fluorescently labeled helical junctions along with NLPB calculations to investigate junction folding and dynamics (13,16).In this study, we use ITC (17) to determine thermodynamic parameters for the folding of the hammerhead ribozyme (18), a three-way RNA helical junction. Recently, Lilley and coworkers reported ITC-measured values for Mg 2+ -binding and coupled folding of the hammerhead ribozyme and two folding mutants (19).…”
mentioning
confidence: 99%
“…FRET at the single molecule level or smFRET is a powerful method to probe dynamic conformational changes and molecular level interactions of biomolecules 29,30 . For example, smFRET studies of the hairpin ribozyme have revealed heterogeneous folding kinetics and have dissected the cleavage and ligation reactions coupled with folding and unfolding reactions 28,[31][32][33] . Here we applied smFRET to the study of the conformational changes and cleavage reactions of a DNAzyme.…”
mentioning
confidence: 99%